Personal income tax progressivity and output volatility: Evidence from OECD countries - Malte Rieth; Cristina Checherita-Westphal; Maria-Grazia Attinasi (Canadian Journal of Economics/Revue canadienne d'économique, 2016)
This paper investigates empirically the effect of personal income tax progressivity on output volatility using macro data from a sample of OECD countries over the period 1982–2009. Our measure of progressivity is based on the difference between the marginal and the average personal income tax rate for the average production worker. We find supportive empirical evidence for the hypothesis that higher personal income tax progressivity leads to lower output volatility. This effect comes in addition to the stabilizing impact of government size and it is equally important in economic terms. All other factors constant, countries with more progressive personal income tax systems seem to benefit from stronger automatic stabilizers.
Keywords: 330